9-PAHSA displays a weak anti-inflammatory potential mediated by specific antagonism of chemokine G protein-coupled receptors - Wohlfart, Paulus; Chehtane, Mounir; Luna, Ernesto; Mehta, Riyaz; Korn, Marcus; Konkar, Anish; Schwahn, Uwe; Petry, Stefan; Tennagels, Norbert; Bielohuby, Maximilian (Frontiers in Drug Discovery, 2023)
9-PAHSA belongs to a class of endogenous mammalian bioactive lipids, fatty acid esters of hydroxy fatty acids (FAHFA), that are present in circulation at nanomolar concentrations in mice and humans.Published preclinical data suggest beneficial effects of 9-PAHSA treatment on glucose metabolism as well as modulation of immune function. However, receptor molecules with high affinity towards these lipids have not been identified so far. In a broad screen of a panel of G protein-coupled receptors (GPCRs) we discovered that 9-PAHSA displays antagonist activity with an IC50 in the micromolar range on selected chemokine receptors, namely CCR6, CCR7, CXCR4 and CXCR5. The potential immunomodulatory activities in a human cellular model of innate immunity were then investigated. In such in vitro experiments, a weak anti-inflammatory potential for high concentrations of 9-PAHSA (10-100 µM) could be detected, as treatment reduced the LPS-induced secretion of certain chemokines, such as CXCL10, MIP-1 beta and MCP. Regarding metabolic effects, we re-investigated 9-PAHSA on glucose metabolism and insulin sensitivity in vitro and in mice confirming conclusions from our earlier study that FAHFAs lack glucoregulatory activity following an acute treatment. Hence, the specific interactions with a subset of chemokine receptors may contribute to weak anti-inflammatory properties of 9-PAHSA, but further studies are needed to confirm its in anti-inflammatory potential in vivo.